The report on the activities of the PAU Commission on the History of Science in 2016/2017 - Michał Kokowski (Studia Historiae Scientiarum)
The report discusses the activities of the Commission on the History of Science of the Polish Academy of Arts and Sciences in 2016/2017. It presents the lists of: scientific meeting, conferences, and new publications.